Safar Perempuan dalam Konteks Sosio-Historis Arab Abad Ke-7: Kritik Hadis Berbasis Sosio-Historis: Women’s Travel in the 7th-Century Arab Socio-Historical Context: A Socio-Historical Approach to Hadith Criticism - Yolan Hardika Pratama; Nurul Huda; Rusdi (AL ISNAD: Journal of Indonesian Hadith Studies, 2026)
This study aims to analyze the hadith regarding the prohibition of women traveling without a maḥram to distinguish between universal ethical principles (maqṣad) and particular-contextual legal applications (ḥukm). The method employed is qualitative library research using a holistic hadith criticism approach. The analysis includes sanad criticism to verify the authenticity of the narration and matan criticism expanded with a socio-historical approach and Maqāṣid al-Syarī‘ah. The findings indicate that the hadiths possess highly authentic sanad quality. However, the analysis of the matan and socio-historical context reveals that the prohibition was a rational protective response to the hazardous conditions of the 7th-century Arabian Peninsula, where a maḥram served as a security guarantor. Thus, the 'illah (legal cause) of this prohibition is the absence of security (amn), not the act of travel itself. This study concludes that in the modern context, where travel security is guaranteed through transportation systems and state law enforcement, the 'illah has ceased to exist, allowing for a review of the ruling. Permitting women to travel safely in the modern era is viewed as more aligned with maqāṣid to realize public interest (maṣlaḥah) and eliminate harm (mafsadah).